Lewenspeil, verlossing van sonde en MIV en VIGS in Suider-Afrika: Gedagtes uit die Gereformeerde tradisie - Murray, Montagu (HTS teologiese studies, 2005)
Standard of living, forgiveness of sins and HIV/aids in Southern Africa: Notions from the Reformed traditionThe article reflects on the relation between standard of living and forgiveness of sins by examining a few significant perspectives from the Reformed tradition. The contemplation results in the invention of a B&S-SCHEME (beggar-and-sinner scheme) recommended by the author as an aid to a more nuanced reflection on theological propositions concerning the relationship between standard of living and the forgiveness of sins. In conclusion, theological propositions on the relationship between a person or group’s HIV-status and guilt and/or innocence before God are examined as an illustration of the application possibility of the B&SSCHEME.